COMPETENT APPROACH TO EVALUATION OF CIVIL SERVANTS UNDER CONDITIONS IMPLEMENTATION OF PROJECT MANAGEMENT - E. Kolesnichenko; Y. Radyukova; D. Eliseyev (Вестник Северо-Кавказского федерального университета, 2022)
The introduction of project management in the structures of state management bodies has become one of the main features of the integrated socio-economic development of the territories. The conformity of the competence and professional skills ofpublic servants with the required conditions is ofparticular importance in the current conditions. The authors proposed a methodology and tools for assessing the competencies of public civil servants in the context of the implementation of the project approach to management. The stages of implementation were: determining the levels offormation (indicators) of competence; Study ofpossible tools for competency assessment; direct evaluation and inference. As the results showed, the most relevant competencies for employees turned out to be: communication, teamwork, stress tolerance, decision-making and the ability to take responsibility, analytical thinking and planning, conflict management.